2012
DOI: 10.3892/or.2012.2050
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of copy number located at 16q22.1: New evidence in mammary ductal carcinoma

Abstract: Copy number variation (CNV) is crucial for gene regulation in humans. A number of studies have revealed that CNV contributes to the initiation and progression of cancer. In this study, we analysed four breast cancer cell lines and six fresh frozen tissues from patients to evaluate the CNV present in the genome using microarray-based comparative genomic hybridization (aCGH). Six genes located at 16q22.1 were analysed by real-time PCR. The real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Han et al used microarray CGH to reveal the existence of a significant association between deletion of 17p12 and resistance to chemotherapy in breast cancer ( 21 ). Sun et al reported that a copy number variation at 16q22.1 in breast cancer is a frequent event ( 22 ). A study performed using 11 primary breast cancers and their matched lymph node metastasis lesions revealed gains on chromosomes 1q, 8q and 17q and losses on chromosomes 6q, 8p, 9q, 13q, 16q, 17p and Xp ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al used microarray CGH to reveal the existence of a significant association between deletion of 17p12 and resistance to chemotherapy in breast cancer ( 21 ). Sun et al reported that a copy number variation at 16q22.1 in breast cancer is a frequent event ( 22 ). A study performed using 11 primary breast cancers and their matched lymph node metastasis lesions revealed gains on chromosomes 1q, 8q and 17q and losses on chromosomes 6q, 8p, 9q, 13q, 16q, 17p and Xp ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that copy number gains or losses are critical genetic factors for diseases. To date, there have been many studies demonstrating that CNVs play important roles in the pathogenetic mechanism of complex diseases, but fewer about their relation with AITD [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is an abnormal growth of cells caused by multiple changes in gene expression leading to dysregulated balance of cell proliferation and cell death and ultimately evolving into a population of cells that can invade tissues and metastasize to distant sites (Ruddon, 2007). Breast cancer is the most frequently diagnosed cancer and is the leading cause of cancer deaths in females worldwide (Sun et al, 2012). Despite continued improvements in diagnosis, surgical techniques and chemotherapy, lethality from breast cancer remains high (Hallet et al, 2013).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%